Economic and Social Determinations of the APBD: A Panel Data Approach in 12 Districts/Cities in East Java 2019–2023 - Octaviana Dwi Chintya; Nur Hidayah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research sought to examine the impact of various determinants, including Gross Regional Domestic Product (PDRB), Rice Agricultural Land Area, Open Unemployment Rate, and Poverty Level, on Regional Revenue and Expenditure Budgets (APBD). The analysis was carried out across 12 districts and cities within East Java Province over a five-year period, specifically from 2019 to 2023. The employed methodology consists of a panel data regression utilizing the most suitable approach, identified as the Random Effect Model (REM). The data utilized were sourced from official agencies such as BPS, BPKAD, and other relevant institutions. The findings indicated that PDRB exerts a positive and significant influence on the budget, suggesting that an increase in regional economic activity correlates with enhanced financial capacity for local governments. Conversely, the Poverty Rate demonstrated a negative and significant impact, indicating that a higher poverty level corresponds to diminished financial capacity within the region. The variables pertaining to Rice Agricultural Land Area and Open Unemployment Rate revealed no significant effect on the budget. These outcomes underscore the importance of economic development and the enhancement of public welfare as pivotal factors for augmenting regional budgets.